Hypoglycaemia Fear among Diabetics - Omar, Shallya; Albsoul, Abla; Alabbadi, Ibrahim (Jordan Journal of Pharmaceutical Sciences, 2016)
Background: This study aimed to evaluate whether fear of hypoglycaemia (FOH) ispresent in diabetic patients receiving oral hypoglycemic agents or insulin and factorsthat can influence it. Methods: This study is a cross sectional survey of diabetic patients attendingendocrine clinics in Jordan University Hospital, King Abdullah University Hospital and Royal Medical Services, from June 2013 till may 2014. Results: Out of 326 approached 268 patients participated. The mean age ofparticipants was (49.81±14.09), and 141 (52.6%) were females. FOH was present in allpatients and with all antidiabetic medications. Among antidiabetic agents, patientstaking insulin were found to have the highest score of overall FOH (p<0.001). Level offear correlated with type of diabetes (p<0.01), and being female (p<0.01). Patientsworking in medical field behavioral fear scores were higher compared with patientsworking in non-medically related field (p<0.01). In addition, as the duration of diabetesincreases the overall FOH increases (p<0.01). It had been found that as the FOHincreases the quality of life decreases (p<0.001). Conclusion: Type of diabetes, age and type of antidiabetic agent affect FOH. Diabetes Mellitus duration and gender affect the behavioral scale of hypoglycaemia fear survey. FOH has been found to affect quality of life.